Acquired cutaneous perforating disorders: Clues to diagnosis by silhouette - Asha Kubba; Meenakshi Batrani; Tanvi Pal (Wolters Kluwer Medknow Publications, 2016)
Inflammatory dermatoses are interpreted by pattern recognition. Primary perforating disorders including reactive perforating collagenosis, elastosis perforans serpiginosa, perforating folliculitis, and Kyrle's disease show clinical and histopathological overlap. This article highlights the importance of architectural based analysis by "silhouette" observed under scanning magnification for diagnosis of primary perforating disorders.